Kyrgyz Republic : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria: Staff Report; Staff Statement and Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kyrgyz Republic. (IMF Staff Country Reports; Country Report, 2011)
The Kyrgyz Republic is emerging from a deep political crisis. In April 2010, a popular uprising toppled the previous regime and internal ethnic conflict in June 2010 exacerbated the already difficult political situation. The crisis has adversely affected economic activity and near-term growth prospects, straining the government's financial position, which has been worsened further by critical reconciliation, recovery, and reconstruction needs. Continued growth in Russia and Kazakhstan, combined with high gold prices, contributed to an expansion in remittances and gold exports by 33 percent and 74 percent, respectively.